(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Cloud computing presents IT organizations with a fundaÂmentally different model of operation, one that takes advantage of the maturity of web applications and networks and the rising interoperability of computing systems to provide IT services. Data security is becoming a core problem in cloud computing, there are some kind of solution that are provide some security with model, some technology. In this paper is attempt to secure data from unauthorized access, the Method of data security is RSA algorithm for providing data security by encrypting the given data based on the KEY combinations. And this data then can only be decrypted by authorized person by using his private key. For the same purpose Google application cloud has been implemented on IJCT Foundation, all data has of IJCT Foundation sifted to Google cloud and RSA security algorithm is implemented by us for secure data.